What Future for Food Regulation? (Milan Law Review, 2022)
The essay aims to examine the new challenges of food regulation, focusing on the need to move beyond the food safety perspective, which aims to ensure the safety of food hygiene, and to adopt the food security perspective, which aims to ensure that everyone has enough food at reasonable prices. After outlining the characteristics of food regulation, the author highlights the contribution of case law to the development of the fundamental "precautionary principle" and the importance of the Green Deal proposed by the European Commission to achieve the fundamental objective of food sustainability.
Keywords: Food regulation; Precautionary principle; Governance; Green Deal